The Effectiveness Of Interactive Power Point Learning Media Towards The Motivation Of Learning To Write Pantun For Class VII Students Of The Masehi Private Junior High School Berastagi 2021/2022 - Hanna Marina Tarigan, Grace; Telaumbanua, Sadieli; Siburian, Panigoran; Trisnton, Teguh (International Journal of Educational Research & Social Sciences, 2022)
The quality of education is very much influenced by factors, where one of the factors that affect the quality of education is the quality of learning in schools and can be seen from the increase in grades. Utilization of media in the learning process in the classroom to make the learning atmosphere fun and can increase student grades. The use of learning media to write rhymes can increase the learning motivation of 7th graders of Berastagi Private Middle School students. It can be seen from the results of simple linear regression testing that the t test significance value is 0.071 less than 0.1and the t regression coefficient is positive, meaning that the more frequent use of interactive learning media, the students' learning motivation will increase. There is a significant difference in value between before the use of interactive learning media and after the use of interactive power point learning media. It can be seen from the test results that the average paired sample difference produces a sig value of 0.000 less than 0.05. The value after using interactive learning media is higher than the value before using interactive power point learning media. Suggestions for further research to add other variables that affect students' learning motivation, because the results of this study indicate that the contribution of learning media to increasing students' learning motivation is only 3.8 percent. Suggestions for teachers to use interactive learning media as a means to deliver material to students, because it is proven that the use of interactive learning media can increase student values and motivation in learning.